Pemanfaatan Tumbuhan Untuk Pengobatan Selama Kehamilan Dan Persalinan Pada Suku Talang Mamak Di Provinsi Riau - Heryudarini Harahap; Mhd. Yunus (Badań Perencanaan Pembangunan Dearth, Penelitian dań Pengembangan Provinsi Riau, 2017)
Utilization of plants as medicinal ingredients has long been done by traditional communities throughout their life cycle in Indonesia, including in Talang Mamak tribe in Riau Province. This paper aimed to provide an overview of how to utilize plants during pregnancy and childbirth in the Talang Mamak tribe in Riau Province in terms of health. The research method was qualitative. The data was collected by documentation study, participant observation, and in-depth interview, which was conducted on Talang Mamak tribe in Indragiri Hulu District. The data analysis was inductive. The study found that the plants used during pregnancy such as coconut oil, gelugur (Garcinia atroviridis Griff.) and yellow flowers (Celosia argentea L), ketari leaf (Curculigo latifolia Dryand.), etc. The plants used during labor were bangun-bangun leaf (Coleus amboinicus Lour), yellow flowers (Celosia argentea L), basil (Ocinum sanctum L), sidingin (Kalanchoe pinnata), etc. The plants were used as external medicine (smeared, burned and sown to the mother), and consumed (soaked in water, raw or cooked). The use of plants and the behavior of pregnant women and maternal mothers was appropriate and not in accordance with the behavior of healthy living.